Strategic Analysis of OMV Petrom in the Romanian Market - Catruc, Vladislav; Kupec, Václav; Písař, Přemysl, 1978-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
In today’s extremely volatile environment, where unpredictability is greater than ever, the need of the strategic analysis for the chosen company has never been more relevant. The main aim of the research is to define strengths, weaknesses, opportunities, and threats of the company OMV Petrom in Romanian fuel retail market. The study is conducted through several research techniques such as Corporate Statements, Stakeholders, PESTEL, Porter Five Forces, Industry Lifecycle, VRIO, and Benchmarking analyses followed by the SWOT framework and Scenario Planning matrix where the main findings are highlighted. The research is followed by recommendations from the author including the increase focus on electric vehicles infrastructure in Romania, constant contact with central authorities, and increase in transparency of company’s operations. The provided suggestions could assist the company in overcoming the challenges and increase its productivity in the current volatile environment.
Vedoucí práce: Václav Kupec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses